2010
DOI: 10.1088/0004-637x/714/1/296
|View full text |Cite
|
Sign up to set email alerts
|

Pulsational Mapping of Calcium Across the Surface of a White Dwarf

Abstract: We constrain the distribution of calcium across the surface of the white dwarf star G29-38 by combining time series spectroscopy from Gemini-North with global time series photometry from the Whole Earth Telescope. G29-38 is actively accreting metals from a known debris disk. Since the metals sink significantly faster than they mix across the surface, any inhomogeneity in the accretion process will appear as an inhomogeneity of the metals on the surface of the star. We measure the flux amplitudes and the calciu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…By studying the pulsation light curve of G29-38, Montgomery (2005) derived the rotation axis (pulsation axis) θ to be 65 • (see Fig. 7 for a cartoon illustration), which is comparable to 55 • derived from comparing the amplitudes of the harmonics (Thompson et al 2010). The white dwarf rotation axis might not be aligned with the axis i of the opaque disk, which is derived to be 30 •1 .…”
Section: External Perturbationmentioning
confidence: 72%
“…By studying the pulsation light curve of G29-38, Montgomery (2005) derived the rotation axis (pulsation axis) θ to be 65 • (see Fig. 7 for a cartoon illustration), which is comparable to 55 • derived from comparing the amplitudes of the harmonics (Thompson et al 2010). The white dwarf rotation axis might not be aligned with the axis i of the opaque disk, which is derived to be 30 •1 .…”
Section: External Perturbationmentioning
confidence: 72%
“…A similar process operates in the intermediate polar class of cataclysmic variable to produce a truncated gaseous accretion disk around the WD (see review of this class in Warner 2003). Based on observations of the Ca II lines during pulsations of the archetype dusty WD G29-38, Thompson et al (2010) have suggested that the Ca is being accreted onto the poles of the WD, rather than equatorially, suggesting that the WD is magnetic. Brinkworth et al (2007) (see the Appendix in that paper) calculated the critical surface charge on a dust grain, Q crit , such that the motion of the dust would be influenced by the WD magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some discussions about whether the accretion from the debris disk occurs as a continuous or a discontinuous process and whether the accreted material follows a particular geometry. In the case of G 29-38, Thompson et al (2010) find a hint that the accretion geometry could be time dependent, pointing to a discontinuous accretion producing spots of heavy elements on the white dwarf surface (see also Montgomery et al 2008) and to the influence of a potential magnetic field on the accretion process. However, the time variability of the heavy element abundances, Ca in the case of G 29-38, which would be the signature of such a discontinuous accretion, was not confirmed (Debes & López-Morales 2008).…”
Section: Numerical Computationsmentioning
confidence: 93%